2022
DOI: 10.4018/joeuc.300766
|View full text |Cite
|
Sign up to set email alerts
|

Predicting User Satisfaction of Mobile Healthcare Services Using Machine Learning

Abstract: Outbreak of the COVID-19 leads to rapid development of the mobile healthcare services. Given that user satisfaction is of great significance in inducing marketing success in competition markets, this research explores and predicts user satisfaction with mobile healthcare services. Specifically, the current research aimed to design a machine learning model that predicts user satisfaction with healthcare services using big data from Google Play Store reviews and satisfaction ratings. By dealing with the sentimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 63 publications
(91 reference statements)
0
4
0
Order By: Relevance
“…They found that a convolutional neural network (CNN) performed the best in this task. In [29,30], machine-learning methods were utilized to improve user satisfaction through application reviews. Along with LightGBM, logistic regression and XGBoost yielded prominent outcomes.…”
Section: Machine Learning For Predictionmentioning
confidence: 99%
“…They found that a convolutional neural network (CNN) performed the best in this task. In [29,30], machine-learning methods were utilized to improve user satisfaction through application reviews. Along with LightGBM, logistic regression and XGBoost yielded prominent outcomes.…”
Section: Machine Learning For Predictionmentioning
confidence: 99%
“…Table 1 shows a summary of related research conducted in diverse domains. Lee et al [13] used algorithms to predict customer satisfaction for mobile health services and demonstrated that extreme gradient boosting (XGBoost) can be adopted to forecast users' sentiments. To predict sentiment using restaurant feedback on quality and price, Zahoor et al [14] confirmed that Random Forest algorithm has higher accuracy than other algorithms.…”
Section: Applications Of Machine Learning In Various Domainsmentioning
confidence: 99%
“…Furthermore, lack of standardized frameworks for disclosing ESG-related metrics significantly intensifies the challenge of ensuring fairness and credibility [3,4]. Considering the escalating volume of data in the ESG domain, the growing importance of advanced natural language processing (NLP) techniques is evident in the effective management and investigation of the comprehensive corpus of unstructured textual data [5,6]. In an endeavor to address these complex challenges, this research engages in the task of proposing a strategy for the objective assessment of corporate open data's ESG scores utilizing automated text-based methodologies.…”
Section: Introductionmentioning
confidence: 99%